The Effectiveness of PPK Religiosity Through Habituation of Duha Prayers in Forming The Discipline Character of Students in MTs. Manba'ul Qur’an of Mojokerto - Ani qoh; Muhammad Fazlurrahman Hadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The Effectiveness of PPK Religiosity through Duha Prayer Habit in Forming Discipline Character of Students in MTs. Manba'ul Qur-an, Mojokerto City, Thesis of Islamic Education Study Program, Postgraduate Program, Muhammadiyah University of Surabaya. The research is motivated by the existence of character improvement efforts through (PPK). In this case, it specialize the value of religiosity through habituation of duha prayers in forming the disciplinary character of students. This research uses quantitative methods with data collection techniques using questionnaires, interviews and documentation. The sample was taken by applying proportional random sampling technique and data analysis using multiple linear regression analysis with SPSS for windows version 22.0. The results of the study concluded that both PPK religiosity and duha prayer are partially significant in forming the disciplinary character of students. This is proven by the results of the T test with a significance value of 0.000 which is lower than the value of α = (0.05). While the results of the correlation coefficient (R) of 0.800, which means that the influence of PPK religiosity and duha prayer is high or very strong with the measurement parameter of the correlation value from 0.70 to 0.89 which means it has a very strong relationship. This means that PPK religiosity through the habituation of praying duha is simultaneously effective in forming the disciplinary character of students.